Quantifying the impact of vegetation‐based metrics on species persistence when choosing offsets for habitat destruction. Issue 2 (8th October 2020) - Marshall, Erica; Valavi, Roozbeh; Connor, Louise O'; Cadenhead, Natasha; Southwell, Darren; Wintle, Brendan A.; Kujala, Heini
Abstract: Developers are often required by law to offset environmental impacts through targeted conservation actions. Most offset policies specify metrics for calculating offset requirements, usually by assessing vegetation condition. Despite widespread use, there is little evidence to support the effectiveness of vegetation‐based metrics for ensuring biodiversity persistence. We compared long‐term impacts of biodiversity offsetting based on area only; vegetation condition only; area × habitat suitability; and condition × habitat suitability in development and restoration simulations for the Hunter Region of New South Wales, Australia. We simulated development and subsequent offsetting through restoration within a virtual landscape, linking simulations to population viability models for 3 species. Habitat gains did not ensure species persistence. No net loss was achieved when performance of offsetting was assessed in terms of amount of habitat restored, but not when outcomes were assessed in terms of persistence. Maintenance of persistence occurred more often when impacts were avoided, giving further support to better enforce the avoidance stage of the mitigation hierarchy. When development affected areas of high habitat quality for species, persistence could not be guaranteed. Therefore, species must be more explicitly accounted for in offsets, rather than just vegetation or habitat alone. Declines due to a failure to account directly for species population dynamics and connectivity overshadowed the benefits delivered by producing large areas of high‐quality habitat. Our modeling framework showed that the benefits delivered by offsets are species specific and that simple vegetation‐based metrics can give misguided impressions on how well biodiversity offsets achieve no net loss. Abstract : Article impact statement : It is important to use offset metrics that account for the impacts of development on long‐term species persistence. Abstract : Cuantificación del Impacto de las Medidas Basadas en la Vegetación sobre la Persistencia de las Especies cuando se Eligen las Compensaciones por la Destrucción del Hábitat Resumen: Con frecuencia se requiere por ley que los desarrolladores compensen los impactos ambientales por medio de acciones de conservación. La mayoría de las políticas de compensación especifican medidas para calcular los requerimientos de cada compensación, generalmente mediante la evaluación de las condiciones de la vegetación. A pesar del uso extenso de estas medidas basadas en la vegetación, existe muy poca evidencia que respalde su efectividad para asegurar la persistencia de la biodiversidad. Comparamos los impactos a largo plazo de las compensaciones de biodiversidad basadas solamente en el área; solamente en la condición de la vegetación; la idoneidad del área x hábitat; y la idoneidad condición x hábitat en las simulaciones de desarrollo y restauración para la Región Hunter de Nueva Gales del Sur, Australia. Simulamos el desarrollo y las compensaciones subsecuentes mediante la restauración dentro de un paisaje virtual, conectando las simulaciones con los modelos de viabilidad poblacional para tres especies. Las ganancias del hábitat no aseguraron la persistencia de las especies. No hubo pérdida neta cuando el desempeño de las compensaciones se evaluó en relación con la persistencia. El mantenimiento de la persistencia ocurrió más seguido cuando se evitaron los impactos, lo que proporciona un mayor respaldo para mejorar la aplicación de la fase de prevención de la jerarquía de mitigación. Cuando el desarrollo afectó a las áreas con una alta calidad de hábitat para las especies, no se pudo garantizar la persistencia. Por lo tanto, las especies deben considerarse más explícitamente en las compensaciones, en lugar de sólo considerar a la vegetación o al hábitat. Las declinaciones causadas por la falta de consideración directa de las dinámicas poblacionales de las especies y de la conectividad opacaron los beneficios producidos por las grandes áreas de hábitat de alta calidad. Nuestro marco de trabajo para el modelado demostró que los beneficios producidos por las compensaciones son específicos para cada especie y que las medidas simples basadas en la vegetación pueden brindar impresiones mal informadas sobre qué tanto influyen las compensaciones de biodiversidad en la no pérdida neta. 摘要: 法律经常要求开发商通过有针对性的保护行动来抵消对环境的影响。大多数生物多样补偿政策明确规定了计算补偿量需求的指标, 通常都是基于对植被条件的评估。这类基于植被的指标虽然已经得到广泛使用, 但其在确保生物多样性续存方面的有效性却几乎没有证据支持。本研究模拟了澳大利亚新南威尔士州猎人区的开发和恢复情况, 并分别从面积、植被条件、地区及生境的适宜性、植被条件及生境的适应性这几个方面比较了生物多样性补偿措施的长期影响。我们在一个虚拟景观中模拟了开发及随后通过恢复得到的补偿, 并将模拟情况与 3 个物种的种群生存模型进行整合。结果显示, 如果以恢复生境的数量来评价补偿效果, 则可以实现无净损失; 但如果以物种续存来进行评价, 则不能实现。在避免影响的情况下, 物种更有可能续存, 这一结果为更好地执行减缓影响层级结构中的避免影响阶段提供了进一步支持。当发展影响到物种高质量生境的区域时, 不能保证物种续存。因此, 必须更明确地将物种纳入补偿机制中, 而不仅仅是考虑植被或生境。因未能直接考虑物种种群动态和连接度而导致的种群数量下降的影响, 会超出制造大面积高质量生境带来的好处。我们的模型框架表明, 生物多样性补偿带来的好处是物种特异的, 而简单的基于植被的指标可能会误导人们, 使其对生物多样性补偿在多大程度上实现了无净损失产生错误印象。【翻译: 胡怡思; 审校: 聂永刚】